Recovering and restoring tampered RFID data using steganographic principles - Mohan, M.; Potdar, Vidyasagar; Chang, Elizabeth (IEEE Computer Society Press, 2006)
Security is one major issue with RFID technology. Mainstream research in RFID security addresses the following security properties i.e. anonymity, confidentiality and authenticity, however it does not cater for integrity. In this paper we consider the fourth security property i.e. integrity. We try to solve the issue of data recovery after RFID data has been tampered. To address this issue, we present a novel steganographic solution, which embeds a secret pattern in the serial number partition of the RFID tag. This secret pattern is the data that we assume would most likely be the candidate for tampering, for example the manufacturer?s and products details stored on the RFID tag. The main motivation for an attacker to tamper this data would be economic benefits like low logistics cost, or quicker custom clearance, and this can only be achieved by changing product details or manufacturer details on the RFID tag. The novelty of this scheme lies in the fact that we have applied steganographic principles to RFID tags; in comparison, most of the existing steganographic solutions are limited to images, or audio, or video applications. We term this scheme ResTamp because it is restores tampered data. This paper provides a detailed theoretical foundation for the ResTamp algorithm.